PENGARUH MEDIA LETING (BOOKLET STUNTING) TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG STUNTING : PENGARUH MEDIA LETING (BOOKLET STUNTING) TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG STUNTING - Linda, Linda; panji; Ningsih, Lisma (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2022)
Background: Stunting or short is a condition of failure to thrive in children under five years of age due to chronic malnutrition and repeated infections, especially in the first 1000 days of life. Stunting is caused by multidimensional factors and is not only caused by poor nutrition experienced by pregnant women and children under five. A total of 94 toddlers in the city of Bengkulu experienced stunting with a prevalence of 4.68% and most were found at Jalan Gedang Health Center as many as 14 toddlers stunting with a prevalence of 14.89%. This study aims to determine the effect of LETING media on knowledge and attitudes about stunting in students of SMKN 5 Bengkulu City. Method: This type of research is Pre Experimental with research one group pretest-posttest design. The sample in this study were students of SMKN 5 Bengkulu City, totaling 32 people using purposive sampling technique. Data analysis in this study used the Wilcoxon signed rank test.. Result: The results of the study obtained the average knowledge before 11.06 and after 13.88 while the average attitude before and after was 43.72 55.75. The results of the Wilcoxon signed rank test obtained p value = 0.000 < 0.005 which shows that there is an influence of LETING media on knowledge and attitudes about stunting in adolescents at SMKN 5 Bengkulu City. This research is expected to be used as one of the learning media in the classroom to provide health promotion so that students' knowledge and attitudes can increase so as to prevent stunting.